The Principal Salivary Gland Is the Primary Source of Digestive Enzymes in the Saliva of the Brown Marmorated Stink Bug, Halyomorpha halys - Liu, Sijun; Bonning, Bryony C. (Frontiers in Physiology, 2019)
The brown marmorated stink bug, Halyomorpha halys, is an invasive, phytophagous stink bug of global importance for agriculture. Tissue-specific transcriptomic analysis of the accessory salivary gland, principal salivary gland and gut resulted in identification of 234 putative protease and 166 putative nuclease sequences. By mapping the previously reported proteomes of H. halys watery saliva and sheath saliva to protein sequences translated from the assembled transcripts, 22 proteases and 2 nucleases in the saliva were identified. Of these, 19 proteases and both nucleases were present in the watery saliva. The majority of proteases and nucleases found in watery saliva were derived from the principal salivary gland, in line with ultrastructural observations, which suggest active protein synthesis and secretion by this tissue. The highly transcribed digestive proteases and nucleases of H. halys were similar to those of the southern green stink bug, Nezara viridula, indicating that these pentatomid stink bugs utilize a similar suite of proteases and nucleases for digestion of plant material. The comprehensive data set for the H. halys salivary glands and gut generated by this study provides an additional resource for further understanding of the biology of this pestiferous species.